LEADERSHIP PROFILE OF MANAGERS IN PUBLIC INSTITUTIONS: CASE STUDY IN THE MUNICIPAL DEPARTMENT OF EDUCATION OF EIRUNEPÉ-AM - de Araújo, Gleiany Rodrigues; Fialho, Rayla da Silva; da Silva, Rosiene Menezes; Falcão, Maria Tânia Portela; da Costa, Endila Maria Ferreira; Lobo, Silviana de Lima; Magalhães, Cilene Farias Batista; Reis, Gustavo Costa (Seven Editora, 2025)
This article investigates the leadership profile of school managers in the municipal education network of Eirunepé-AM, aiming to understand how these leaders influence school planning and the quality of education. The research is exploratory in nature, with bibliographic and field approaches, and used a questionnaire applied to 14 managers linked to the Municipal Department of Education (SEMEC) as the data collection instrument. The study considers that the leadership exercised by school managers is a determining factor for effective, participatory management focused on positive pedagogical outcomes. The collected data made it possible to identify the predominant leadership styles, as well as the main challenges faced by managers in their daily school routines. The results highlight the need for continued training of educational leaders, with an emphasis on management skills, strategic planning, and decision-making. The study contributes to the strengthening of school management and provides support for the development of more effective educational public policies aligned with local demands.DOI: https://doi.org/10.56238/sevened2025.021-030